Comparison of diagnostic qualities of radiographs indirectly digitized using scan and digital camera techniques - Ehsan Hekmatian; Ahmad Beigi; Jaber Yaghini (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Advent of digital imaging technology revolutionized radiology science, one aspect of which is indirect digital imaging technique. In this technique scanners or digital cameras are used to digitize radiographs. The aim of this research was to compare diagnostic quality of conventional periapical radiographs digitized with scanners and cameras.Materials and methods: In this in vitro study 40 radiographs were digitized with two scanners and two cameras in the six following methods: 3- and 5-Megapixel Fuji digital cameras, 5 -MP Canon digital camera, 450 dot per inch and 600 dpi Epson scanners and 600 dpi HP scanners. A total of 240 images were prepared. Four specialists and general dental practitioners were asked to observe 4 anatomic landmarks (periodontal ligament, root apex, lamina dura and cancellous bone) on the conventional and digitized radiographs, score the qualities from 1 to 3 and record them in a check list. SPSS software was used for data analysis by ANOVA and Friedman and Wilcoxon tests.(α = 0.05)Results: Analog radiographs received higher scores compared to the two digitization techniques (p value < 0.001), with higher diagnostic value scores for the images of the digital cameras (p value < 0.001). Conclusion: Analog images were superior to digital images in the present study. It appears the habitual and repeated visualization of conventional radiographs and the quality and age of the cameras, scanners and monitors used in this study all had an influence on the results. Key words: Digital camera, Indirect digital imaging technique, Periapical radiography, Scanner